Auditory Feedback of False Heart Rate for Video Game Experience Improvement - Ogawa, Sayaka; Fujiwara, Koichi; Kano, Manabu (IEEE transactions on affective computing, 2023)
Changes in emotions affect our physiological responses, and perhaps vice versa. We investigate a new game interaction system that uses false heart rate (fHR) feedback to improve the player experience (PX). The fHR feedback presents false HR information to players so that they perceive changes in the presented HR as being a result of alteration in PX. We introduced auditory fHR feedback into game interaction and investigated its effects through an experiment. Participants repeated gameplay of an action game while hearing heartbeat-like sounds and answered questionnaires regarding PX. Some participants heard the heartbeat-like sounds synchronized with their actual HR, whereas others heard the heartbeat-like sounds whose tempo became gradually faster or slower than their actual HR. The results indicated that an accelerating fHR feedback pattern with +5 bpm/min was appropriate for improving PX; participants were able to maintain their motivation to continue the game. The experiment also indicated that it is necessary for participants to perceive the presented heartbeat-like sounds as reflecting their actual HR. Participants did not maintain their motivation when they were told that the presented sounds were not correlated with their actual HR. The present work provides new principles for video game interaction design based on physiological measurements.